2011
DOI: 10.1007/s00702-011-0722-6
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine, but not olanzapine, disrupts conditioned avoidance response in rats by antagonizing 5-HT2A/2C receptors

Abstract: The present study was designed to assess the role of 5-HT2A/2C receptors in the acute and repeated effect of clozapine and olanzapine in a rat conditioned avoidance response model (CAR), a validated model of antipsychotic activity. Male Sprague-Dawley rats that were previously treated with either phencyclidine (0.5-2.0 mg/kg, sc), amphetamine (1.25-5.0 mg/kg, sc), or saline and tested in a prepulse inhibition of acoustic startle study were used. They were first trained to acquire avoidance response to a white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 38 publications
7
54
0
Order By: Relevance
“…What account for their differences is not entirely clear. On the basis of our previous work on the neuroceptor mechanisms of OLZ sensitization and CLZ tolerance in adult rats Li et al, 2012), we speculate that their differential (even opposing) actions on dopamine D 2/3 receptors may be one of the factors, as we show that pretreatment of quinpirole, a selective D 2 /D 3 dopaminergic receptor agonist, attenuated OLZ sensitization but enhanced CLZ tolerance on avoidance response. Future work should investigate the role of dopamine D 2/3 receptors in the mediation of OLZ sensitization and CLZ tolerance in adolescence.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…What account for their differences is not entirely clear. On the basis of our previous work on the neuroceptor mechanisms of OLZ sensitization and CLZ tolerance in adult rats Li et al, 2012), we speculate that their differential (even opposing) actions on dopamine D 2/3 receptors may be one of the factors, as we show that pretreatment of quinpirole, a selective D 2 /D 3 dopaminergic receptor agonist, attenuated OLZ sensitization but enhanced CLZ tolerance on avoidance response. Future work should investigate the role of dopamine D 2/3 receptors in the mediation of OLZ sensitization and CLZ tolerance in adolescence.…”
Section: Discussionsupporting
confidence: 53%
“…The answer to both questions is yes. We demonstrated that OLZ sensitization and CLZ tolerance could be induced in adolescent rats using the same procedure (ie, an induction phase followed by a challenge test) as employed in adult rats (Li et al, 2004;Li et al, 2007;Li et al, 2009a;Li et al, 2009b;Li et al, 2010;Mead and Li, 2010;Li et al, 2012;Zhang and Li, 2012). They mainly manifested in the avoidance response (a behavioral measure of antipsychotic activity) and/or intertrial crossing (a behavioral measure of motor function/sedation), but not in the 22 kHz USV (an index of anxiolytic property), suggesting that they are behaviorally specific (Stewart and Badiani, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations